Dynamics Relationship of Phyllosphere and Rhizosphere Bacterial Communities During the Development of Bothriochloa ischaemum in Copper Tailings - Jia, Tong; Yao, Yushan; Wang, Ruihong; Wu, Tiehang; Chai, Baofeng (Frontiers in Microbiology, 2020)
Copper mining and the byproducts associated with the industry have led to serious pollution in the Loess Plateau of China. There is a potential in improving the ecological restoration efficiency of such degraded land through combining microbial and plant remediation approaches. However, the community structure and function of phyllosphere and rhizosphere microorganisms and their response to plant development in copper tailings dams are poorly understood. This study investigated the impact of the phyllosphere and rhizosphere microbial communities on Bothriochloa ischaemum during three distinct plant development stages: seedling, tiller, and mature. The relative species abundance and Shannon index of bacterial communities of the rhizosphere during the seedling and tiller stages were distinct from that in the mature stage. Dominant bacteria at the level of phyla, such as Proteobacteria, Cyanobacteria, Actinobacteria, and Bacteroidetes, followed distinct patterns associated with plant development in the phyllosphere, but the predominant bacteria were similar in the rhizosphere. Redundancy analysis showed that aboveground total nitrogen and the carbon and nitrogen ratio of this plant species significantly affected phyllosphere bacterial community structure, whereas soil water content, soil nutrients, electrical conductivity and salinity significantly affected rhizosphere bacterial community structure. Moreover, keystone phyllosphere and rhizosphere bacterial species differed significantly. This study sheds new light on understanding the dynamics relationship of phyllosphere and rhizosphere bacterial communities during plant development in copper tailings. These results are beneficial to the development and utilization of beneficial microbial communities at different stages of development, which might help to reclaim and stabilize tailings more effectively.